Varied Susceptibility of Five Echinochloa Species to Herbicides and Molecular Identification of Species Using CDDP Markers - Xiaoyan Wang; Lulu Ye; Jingui Zhou; Jun Li (Agronomy, 2025)
Echinochloa spp. are among the most problematic malignant weeds in paddy fields. Under long-term herbicide selection pressure, they have developed resistances to multiple herbicides, leading to diminished control efficacy. Precision herbicide application, tailored to the susceptibility disparities among Echinochloa species, has emerged as a promising strategy to enhance weed control efficacy and decelerate herbicide resistance development. Nevertheless, the herbicide susceptibility variation across different Echinochloa taxa remain uncharted. Therefore, in this study, we determined the susceptibility of five Echinochloa species to 15 commonly used herbicides using the whole-plant bioassay method. Additionally, we explored the feasibility of employing the CDDP molecular marker technique for the rapid identification of distinct Echinochloa species. The results showing that five Echinochloa species exhibited differential susceptibility to 12 of the 15 herbicides tested underscore the necessity of personalized herbicide application strategies. Among the seven CDDP markers, KNOX-3 generated a specific band in the Echinochloa caudata population, which can be used to distinguish it from the other four Echinochloa species. The findings of this study will facilitate the precision application of herbicides for Echinochloa management in paddy fields.